2016
DOI: 10.1111/jvp.12374
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of formalin‐induced pain‐related behaviour by clonidine and yohimbine in the Speke's hinged tortoise (Kiniskys spekii)

Abstract: The study was designed to investigate the involvement of noradrenergic and serotonergic receptor systems in the modulation of formalin-induced pain-related behaviour in the Speke's hinged tortoise. Intradermal injection of 100 μL of formalin at a dilution of 12.5% caused pain-related behaviour (hindlimb withdrawal) that lasted for a mean time of 19.28 min (monophasic response). Intrathecal administration of clonidine (α -adrenergic receptor agonist) and yohimbine (α -adrenergic receptor antagonist) at a dose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Moreover, damage or loss of LC noradrenergic neurons could result in the decrease of NE in the central nervous system (Marien et al, 2004 ; Rommelfanger and Weinshenker, 2007 ; Weinshenker, 2008 ). In our study, we found yohimbine, α 2 -AR antagonist (Makau et al, 2016 ), significantly increased the peak value of elicited NE release from noradrenergic nerve fibers in the PVN evoked by electrical stimulation in LC in the CUMS rats. It is generally recognized that the α2-adrenergic receptors are coupled with the inhibitory guanosine triphosphate (GTP)-binding protein, which may be involved in the receptor-mediated transmembrane signaling by regulating adenylate cyclase activity (Tsuda et al, 2003 ).…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, damage or loss of LC noradrenergic neurons could result in the decrease of NE in the central nervous system (Marien et al, 2004 ; Rommelfanger and Weinshenker, 2007 ; Weinshenker, 2008 ). In our study, we found yohimbine, α 2 -AR antagonist (Makau et al, 2016 ), significantly increased the peak value of elicited NE release from noradrenergic nerve fibers in the PVN evoked by electrical stimulation in LC in the CUMS rats. It is generally recognized that the α2-adrenergic receptors are coupled with the inhibitory guanosine triphosphate (GTP)-binding protein, which may be involved in the receptor-mediated transmembrane signaling by regulating adenylate cyclase activity (Tsuda et al, 2003 ).…”
Section: Discussionsupporting
confidence: 61%
“…Intraperitoneal administration of clonidine under formalin test responds in a similar dose dependent manner in mice and rats ( Yoon et al., 2015 ; Fukuda et al., 2006 ). Clonidine administration intrathecally also shows similar dose dependent responses under formalin test in the African marsh terrapin ( Pelomedusa subrufa ) and Speke's hinged tortoise ( Makau et al., 2014 , 2016 ); mice ( Kanui et al., 1993 ), and Sprague-Dawley rats ( Yoon et al., 2009 ).…”
Section: Discussionmentioning
confidence: 83%
“…In the current study, administration of 30 μg/kg yohimbine significantly reversed the effects of 3 μg/kg clonidine during the late phase of formalin test. Yohimbine is reported to show similar antagonistic effects to clonidine even in humans ( Charney et al., 1983 ), rats ( Normansell and Panksepp, 1985 ), marsh terrapins ( Makau et al., 2014 ) and tortoises ( Makau et al., 2016 ). Yohimbine acts by presynaptically inhibiting alpha-2 adrenergic receptors ( Mekkaw and Al-Badr, 1987 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations